KEPUTUSAN PEMBELIAN BERBASIS BRAND IMAGE DAN KUALITAS PELAYANAN DITINJAU DARI PERSPEKTIF DESAIN - Puji Solikhah; Ambar Lukitaningsih (Universitas Sarjanawiyata Tamansiswa, 2017)
This study aims to: 1) Determine the influence of brand image and service quality on purchasing decisions 2) Knowing the interaction effect of the design to the purchasing decision. This research was conducted at the Art Shop Borobudur Silver in Magelang, populations are consumers who buy at Borobudur Silver Art Shop Magelang, sampling used purposive sampling technique. The analytical tool used Patial Least Square (PLS), the SEM-based variance, with software SmartPLS 3.0. The results showed that: 1) Brand Image (X1) positive and significant impact on the purchase decision (Y) in the Art Shop Borobudur Silver Magelang proved the value P.Sig (0.000). 2) Quality of Service (X2) positive and significant impact on the Purchase decision (Y) in the Art Shop Magelang Borobudur Silver proved the value P.Sig (0000) .3) Brand Image (X1) and Quality of Service (X2) positive and significant impact on the purchase decision (Y) in the Art Shop Borobudur Silver Magelang proved the value P.Sig (0000). 4) Design (Z) does not moderate the effect of Brand Image (X1) of the Purchase Decision (Y) at the Art Shop Borobudur Silver, Magelang. This can be seen from P Values 0834 (> 0.05) and the coefficient parameters -0016 (Tstatistik0.194 <Ttabel 1661).Keywords: brand image, quality of service, design, purchasing decisions